Revolution in miniature : - Braun, Ernest (Cambridge University Press, 1982)
Semiconductor electronics is the major technology of our age. This revised and up dated edition is a basic contribution to the discussion of its history and impact by authors who have long studied the process of technological change and who are familiar with the peculiarities of the industry.